2015
DOI: 10.1002/sca.21250
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive noise Wiener filter for scanning electron microscope imaging system

Abstract: Noise on scanning electron microscope (SEM) images is studied. Gaussian noise is the most common type of noise in SEM image. We developed a new noise reduction filter based on the Wiener filter. We compared the performance of this new filter namely adaptive noise Wiener (ANW) filter, with four common existing filters as well as average filter, median filter, Gaussian smoothing filter and the Wiener filter. Based on the experiments results the proposed new filter has better performance on different noise varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A new Wiener based filter, named adaptive noise Wiener filter, was developed by Sim et al . (). In order to improve the performance of original Wiener filter, noise variance was included to it.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A new Wiener based filter, named adaptive noise Wiener filter, was developed by Sim et al . (). In order to improve the performance of original Wiener filter, noise variance was included to it.…”
Section: Introductionmentioning
confidence: 97%
“…Many noise removal techniques have been introduced to enhance the quality of images corrupted by noise, but because of some characteristics of different techniques, for example, dependency on image structure, presence of different processing parameters, and degradation of image important details, they can only be used in some special fields. Several different noise reduction approaches have been proposed in SEM field (Herzog et al ., ; Yew and Pease, ; Lewis and Sakrison, ; Oron and Gilbert, ; Jones and Smith, ; Oho et al ., , ; Yano and Nomura, ; Sim et al ., , , ; Kiani et al ., ). Different filters use various approaches to achieve this aim.…”
Section: Introductionmentioning
confidence: 99%
“…With four commonly existing filters it matched the enactment of this novel filter namely adaptive noise Wiener (ANW) filter. Investigational conclusions demonstrate that the suggested new filter has enhanced performance on different noise variance comparing to the other existing noise removal filters in the experiments [27]. It proposed deblurring method which is performed by using the Wiener filter.…”
Section: E Wiener Filtermentioning
confidence: 99%
“…For Transmission Electron Microscopy (TEM) images, several digital filters have been introduced by Kushwaha et al 7 such as median or Wiener filter. A similar work proposed by Sim et al 8 and Aguirre 9 based on employing an adaptive Wiener filter to enhance the effectiveness of the classical Wiener filter by considering the noise variance. Luisier et al 10 have suggested a Poisson Unbiased Risk Estimation-Linear Expansion of Thresholds (PURE-LET) technique for denoising images corrupted with Poisson noise.…”
Section: Introductionmentioning
confidence: 99%